Factor’s Influence Analysis of Frost Heave during the Twin-Tunnel Construction Using Artificial Horizontal Ground Freezing Method - Rong-bao Hong; Hai-bing Cai; Meng-kai Li; Ya-ru Li (Advances in Civil Engineering)
In order to analyze the influence of different twin-tunnel parameters on the frost heave of the ground, six tunnel clear distances (0.25 D, 1.00 D, 1.50 D, 2.00 D, 2.50 D, and 3.00 d), three tunnel buried depths (6 m, 12 m, and 18 m), and two freezing orders (simultaneous freezing and sequential freezing) are selected to establish the two-dimensional numerical calculation models, using ABAQUS finite-element program and the user subroutine of frost heaving deformation, and considering the orthotropic deformation characteristics of frozen soil. Numerical simulation results show that the interaction of twin-tunnel freezing is weakened with the increase in tunnel clear distance. Correspondingly, the heaving displacement of the ground surface also decreases. Besides, the heaving displacement curve of the ground surface gradually changes from the unimodal N-type to bimodal M-type as the tunnel clear distance increases. However, the trough of the bimodal M-type curve gradually disappears as the tunnel buried depth increases. SPSS mathematical analysis results show that tunnel clear distance has the highest significance, tunnel buried depth ranks the second, and freezing order ranks the last. It is important to select the appropriate tunnel clear distance during the design of the twin-tunnel construction using the artificial horizontal ground freezing method.